Comparative evaluation of arch length and palatal depth between four different bone borne rapid palatal expanders in bilateral cleft lip and palate patients: A three -dimensional finite element analysis - Bajpai, Sakshi; Balani, Rajesh Kumar; Kallury, Amitabh; Dubey, Chandrika; Katiyar, Aakriti; Chavan, Utkarsha (Journal of Neonatal Surgery, 2025)
Background: Bilateral cleft lip and palate (BCLP) patients commonly exhibit maxillary transverse deficiency, reduced arch dimensions, and altered palatal morphology. Bone-borne rapid palatal expanders have been introduced to achieve greater skeletal effects with fewer dentoalveolar side effects. However, limited evidence exists comparing their effects on arch length and palatal depth in cleft patients using three-dimensional finite element analysis (FEA). Aim: To comparatively evaluate arch length and palatal depth among four different bone-borne rapid palatal expanders in bilateral cleft lip and palate patients using three-dimensional finite element analysis. Materials and Methods: A three-dimensional finite element model of a bilateral cleft lip and palate maxilla was constructed from cone-beam computed tomography data. Four different bone-borne rapid palatal expander designs were virtually adapted to the model. Standardized expansion forces were applied under identical simulation conditions. Result: All four bone-borne expanders produced measurable changes in arch length and palatal depth, though the magnitude and pattern of change varied among the designs. Expanders with greater skeletal anchorage demonstrated more favorable and controlled alterations, indicating differences in biomechanical efficiency between appliances. Conclusion: Bone-borne rapid palatal expanders showed differing effects on arch length and palatal depth in BCLP patients. Three-dimensional FEA is a valuable tool for comparing appliance biomechanics and may aid in selecting the most effective expander design